The ErbB Receptors and Associated Key Signalling Proteins in Cancer - Al-Janabi, Ismail (AL-Kindy College Medical Journal, 2026)
Cancer is a disease of almost all multicellular organisms, in which communication between cells plays a crucial role in the life and development of that organism. The ErbB family of tyrosine kinase receptors plays a fundamental part in signal transmission, controlling cell proliferation and survival. Signalling outputs of the ErbB receptors are tightly controlled under normal physiological conditions. However, genomic amplification, overexpression or mutational activation of these receptors and their signalling proteins is a common cause of cancer. This narrative review provides an overview of the structure, activation, and modes by which these receptors are dysregulated in oncogenesis. The critical downstream signalling pathways of RAS/RAF/MEK/ERK governing proliferation and PI3K/AKT/mTOR controlling survival are detailed. We discuss the development of ErbB-targeted therapies with emphasis on monoclonal antibodies and tyrosine kinase inhibitors and address the major challenge of therapy resistance. Next-generation tyrosine kinase inhibitors and combination therapies aimed at overcoming treatment failures are also outlined.